Gyrodactylus species (Monogenea: Gyrodactylidae) on the cichlid fishes of Senegal, with the description of Gyrodactylus ergensi n. sp. from Mango tilapia, Sarotherodon galilaeus L. (Teleostei: Cichilidae) - Prikrylová, Iva; Matejusová, Iveta; Musilová, Nad'a; Gelnar, Milan (Parasitology research, 2009)
The first record of Gyrodactylus species Nordmann, 1832 on the cichlid fish from Senegal is reported. Gyrodactylus parasites were found on four host species studied, Hemichromis fasciatus, Hemichromis letournaeuxi, Oreochromis niloticus, and Sarotherodon galilaeus. Gyrodactylus cichlidarum Paperna (Bamidgeh 13:14-29, 1968) were collected from H. fasciatus, and its identity was confirmed based on the morphometrical comparison with the holotype specimens of G. cichlidarum. Only one specimen of Gyrodactylus sp. was noted on H. letournaeuxi. The gyrodactylid specimens on O. niloticus and S. galilaeus were described as Gyrodactylus ergensi n. sp. based on the detailed morphometrical analysis supported by sequencing. The haptoral sclerites of G. ergensi n. sp., which closely resemble those of Gyrodactylus nyanzae Paperna, 1973, are compared with the type material and discussed. A partial sequence of the internal transcribed spacer recombinant DNA (ITS rDNA) was obtained from two specimens of G. ergensi, and a close relationship between G. ergensi n. sp. and G. cichlidarum is suggested based on 92% similarity in ITS rDNA region.
Keywords: Senegal; mezerníky ribozomální DNA; Animals; DNA, Helminth; ploštěnci; Sequence Analysis, DNA; Phylogeny; Platyhelminths; DNA, Ribosomal Spacer; Molecular Sequence Data; Cichlids; molekulární sekvence - údaje; zvířata; sekvenční analýza DNA; cichlidy; DNA helmintů; fylogeneze